Aerobic composting of digested residue eluted from dry methane fermentation to develop a zero-emission process. (March 2017) - Huang, Yu-Lian; Sun, Zhao-Yong; Zhong, Xiao-Zhong; Wang, Ting-Ting; Tan, Li; Tang, Yue-Qin; Kida, Kenji
Highlights: Composting digested residue eluted from dry methane fermentation. The NO3 − content in the end-product was 9.7 g kg −1 -TS and GI reached 151%. Occurrence of nitrification was attributed to AOB activity. Zero-emission process for producing ethanol-methane-compost from kitchen garbage. Abstract: Digested residue remained at the end of a process for the production of fuel ethanol and methane from kitchen garbage. To develop a zero-emission process, the compostability of the digested residue was assessed to obtain an added-value fertilizer. Composting of the digested residue by adding matured compost and a bulking agent was performed using a lab-scale composting reactor. The composting process showed that volatile total solid (VTS) degradation mainly occurred during the first 13 days, and the highest VTS degradation efficiency was about 27% at the end. The raw material was not suitable as a fertilizer due to its high NH4 + and volatile fatty acids (VFAs) concentration. However, the composting process produced remarkable results; the physicochemical properties indicated that highly matured compost was obtained within 62 days of the composting process, and the final N concentration, NO3 − concentration, and the germination index (GI) at the end of the composting process was 16.4 g kg −1 -TS, 9.7 g kg −1 -TS, and 151%, respectively. Real-time quantitative PCR ( q PCR) analysis of ammonia oxidizers indicated that the occurrence of nitrification during the composting of digested residue was attributed to the activity of ammonia-oxidizing bacteria (AOB).